Cyclic Behavior and Modeling of Bolted Glulam Joint with Cracks Loaded Parallel to Grain - Jing Zhang; Zhi-Fang Liu; Yong Xu; Mai-Li Zhang; Liu-Cheng Mo (Advances in Civil Engineering)
Under varying humidity and temperature conditions, with the constraint of metal fasteners to wood shrinkage, cracks along the bolt lines are generally observed in bolted glulam joints. A three-dimensional (3D) numerical model was established in software package ANSYS to investigate the cyclic behavior of bolted glulam joints with local cracks. A reversed cyclic loading was applied in the parallel-to-grain direction. The accuracy of numerical simulation was proved by comparison with full-scale experimental results. Typical failure modes were reproduced in the numerical analysis with the application of wood foundation zone material model and cohesive zone material model. The effect of crack number and length on the hysteretic behavior of bolted glulam joints was quantified by a parametric study. It was found that initial cracks impair the peak capacity and elastic stiffness of bolted glulam joints significantly. More decrease in capacity was observed in joints with more cracks, and longer cracks affect elastic stiffness more dramatically. Moreover, with the existence of initial cracks, the energy dissipated and equivalent viscous damping ratio of bolted joints are reduced by 24% and 13.3%, respectively.